2006
DOI: 10.1111/j.1744-7348.2005.00037.x
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of single and multiple species flower patches to beneficial insects in agroecosystems

Abstract: The provision of floral resources for the enhancement of beneficial insect populations has shown promise as a strategy to enhance biological control and pollination in agroecosystems. One approach involves the provision of a single flower species while a second involves the multiple flower species, but the two have never been compared experimentally. Here we examine the influence of single and multiple species flower treatments on the abundance and foraging behaviour of key beneficial insects in two agricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 41 publications
(48 reference statements)
0
57
0
1
Order By: Relevance
“…Several studies have observed a higher number of hoverfl ies when introducing fl owering plants in an outdoor crop (Hickman & Wratten 1996;Fitzgerald & Solomon 2004;Pontin et al 2006), but this is the fi rst time that this has been proven for commercial greenhouses. Th e special character of Mediterranean greenhouses makes this possible, as their semi-open structure leads to the natural presence of natural enemies (Gabarra et al 2004;Pineda & MarcosGarcía 2008a).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have observed a higher number of hoverfl ies when introducing fl owering plants in an outdoor crop (Hickman & Wratten 1996;Fitzgerald & Solomon 2004;Pontin et al 2006), but this is the fi rst time that this has been proven for commercial greenhouses. Th e special character of Mediterranean greenhouses makes this possible, as their semi-open structure leads to the natural presence of natural enemies (Gabarra et al 2004;Pineda & MarcosGarcía 2008a).…”
Section: Discussionmentioning
confidence: 98%
“…Th is strategy can provide additional ecosystem services, such as the maintenance of biodiversity or pollination (Fiedler et al 2008). Based on this fact, the provision of fl oral resources within or adjacent to crops is a conservation biological control strategy that increases the abundance of benefi cial insects (Frank 1999;Sutherland et al 2001;Pontin et al 2006). It has been demonstrated that fl owering plants can enhance the growth, survival, development and reproduction of some predators and parasitoids (Landis et al 2000;Berndt & Wratten 2005).…”
mentioning
confidence: 99%
“…Lists of declining species include many weeds, which are threatened because they depend on flower visitors for seed set (Motten 1986;Biesmeijer et al 2006). Indeed, rare weed species have difficulties attracting insects and their interactions with pollinators are more fragile (Pontin et al 2006). Thus, stability of weed-insect pollinator networks is essential to maintaining biodiversity in the arable landscapes.…”
Section: Do Generalist Insect Pollinators Serve Weeds Better? Not Alwaysmentioning
confidence: 99%
“…It is well-established that insufficient pollination and biological control services can limit crop production when other factors such as soil nutrients and water are sufficient [21]. Evidence is now emerging to support the theory that pollination and biological control respond to similar drivers, such as floral resources and landscape structure [22][23][24], and it is therefore logical to consider them together.…”
Section: Ecological Intensification and Regulating Ecosystem Servicesmentioning
confidence: 99%